Status of Katchi Class in Relation to Early Childhood Education Policies and practices in Punjab - Jahanara Saif, Attiya Inam, Muhammad Abiodullah (JECCE, 2023)
The study aimed at identifying the present conditions of ECE or traditionally termed ‘katchi class’ at government schools in Punjab (specifically targeting Okara city), while reviewing educational policies and available literature to assess the reasons for non-implementation of the same. After failing to achieve its targets for EFA and MDG’s in regard to ECE specifically, spending a mere 2.3% of its GNP on education (UNESCO, 2014) the status of the katchi class, the most critical stage of learning remains deplorable in government schools of Punjab. Analysis of the physical facilities, classroom practices and teacher assessment, along with interviews of headmasters and 3 district officials, the DCO, EDO (education) and DEO (primary schools) were performed using observation checklists and questionnaires respectively. The quantitative data was represented through simple percentages to draw conclusions to research questions while the qualitative data was thematically analyzed to find out the reasons for non-implementation of NCECE. The results indicated an overall low quality of katchi class both in terms of physical environment and quality of education being offered, along with a lack of government interest and contribution in the field. Financial, organizational and cultural restraints were identified as barriers in the implementation of the policies and recommendations suggested for overcoming them.